Design and Implementation of high - order digital equalizers for audio signal using matlab and dsk tms 320c6711 - Sung, Ho Van (H. : ĐHQGHN, 2017)
In this paper, the transfer function of the seventh order digital graphic equalizer is calculated. The gain responses of the digital filters, of individual equalizers and of overall graphic equalizer are designed by MATLAB and implemented by DSK TMS320C6711. These gains can be controlled independently by adjusting the parameters c, a and p of each section in the digital graphic equalizer.